Endovascular aneurysm repair using fenestrated endoprostheses made to order from the manufacturer: Case report - Sergey A. Abugov; Gordey S. Vlasko; Roman S. Polyakov; Mikhail V. Puretskiy; Gayk V. Mardanyan; Aleksandra A. Pirkova; Dzhul'etta A. Karamyan; Shota G. Chargaziya; Kiazim A. Kur-ipa (ZAO "Consilium Medicum", 2023)
This article presents two clinical cases of endovascular aneurysm repair using fenestrated endografts manufactured by the manufacturer in patients with juxta and pararenal aortic aneurysm. The variants of endovascular approaches to the treatment of pathology were analyzed. Clinical examples show the specifics of the choice and justification for the use of endovascular treatment. The conclusion is made about the effectiveness of the method.